Association of systemic cellullar immunity with the development of cataract - R. E. Osmanov; O. L. Fabrikantov (Медицинская иммунология)
Among the causes of visual impairment, cataract occupies a significant proportion, which indicates a need for studying the causes of its development. Over recent years, an important role has been given to impaired immunoregulatory reactions in its genesis. So far, however, participation of systemic cellular immunity in occurence of different clinical types of cataract remains poorly known. The aim of the present study was to assess association between parameters of systemic cellular immunity and development of mature nuclear cataract. On the basis of IRTC “S.N. Fedorov Eye Microsurgery Center” (Tambov Branch), a study of major immune cells subpopulations in peripheral blood was performed over 2019-2020 in 63 patients aged 60-84 years, suffering from mature nuclear cataract (the study group). The control group consisted of 47 patients aged 60 to 84 years without ocular disorders in the history and at the time of examination. The evaluation of differentiated cell clusters was carried out with BD FACS Canto II flow cytometer. As a result, a statistically significant decrease in the absolute number of CD19+ to 0.18±0.003 × 109 /L was revealed in the patients from the main group versus 0.42±0.05 × 109 /L in controls; the relative number of CD19+ was decreased to 8.36±1.1% versus 19.64±1.3%, respectively, along with absolute content of CD3+ cells of 0.92±0.08 × 109 /L versus 1.57±0.06 × 109 /L in controls. On the contrary, the absolute number of CD56+ in the patients with mature nuclear cataract was significantly increased to 0.27±0.02×109 /L compared to 0.15±0.03 × 109 /L in the age control group. The relative risk values are statistically significant, and the highest levels were found for CD19+ and CD3+ cell clusters, which were 3.237 and 2.954 for the absolute number, and 1.952 and 2.748, for the relative number, respectively. These findings suggest that development of a mature nuclear cataract is associated primarily with a decrease in absolute and relative contents of B and T lymphocytes at the systemic level, which may be of practical importance when used as immunological markers of nuclear cataract.